1997
DOI: 10.1038/sj.bjp.0701185
|View full text |Cite
|
Sign up to set email alerts
|

Protection by dexamethasone of the functional desensitization to β2‐adrenoceptor‐mediated responses in human lung mast cells

Abstract: 1 The b-adrenoceptor agonist, isoprenaline, inhibited the IgE-mediated release of histamine from human lung mast cells (HLMC) in a dose-dependent manner. Maximal inhibitory e ects were obtained with 0.1 mM isoprenaline. However, the inhibition of histamine release from HLMC by isoprenaline (0.1 mM) was highly variable ranging from 33 to 97% inhibition (mean, 59+3%, n=27). 2 Long-term (24 h) incubation of HLMC with isoprenaline led to a subsequent reduction in the ability of a second exposure of isoprenaline to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
1
29
0
1
Order By: Relevance
“…It has been suggested that genetically mediated paradoxical bronchial obstruction or hyperresponsiveness may occur with long-term use of b-agonists [22]. Steroids have shown in experimental in vitro and in vivo studies to reverse functional desensitisation of b 2 -AR [4,23,24], increase receptor expression and density, and enhance expression of G s a, producing a dose-dependent increase in cyclic adenosine monophosphate levels [25,26]. However, in humans, loss of bronchoprotection from regularly administered b 2 -agonists seems to reverse only with acute high doses of ICS [27,28] and it is not clear that this happens with chronic use of ICS at low or medium doses [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that genetically mediated paradoxical bronchial obstruction or hyperresponsiveness may occur with long-term use of b-agonists [22]. Steroids have shown in experimental in vitro and in vivo studies to reverse functional desensitisation of b 2 -AR [4,23,24], increase receptor expression and density, and enhance expression of G s a, producing a dose-dependent increase in cyclic adenosine monophosphate levels [25,26]. However, in humans, loss of bronchoprotection from regularly administered b 2 -agonists seems to reverse only with acute high doses of ICS [27,28] and it is not clear that this happens with chronic use of ICS at low or medium doses [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In asthmatic patients, there is tolerance to the mast cell protective effect of b 2 -agonists (against adenosine and allergen), but not to the protective effect against direct bronchoconstrictors [43,44]. A corticosteroid can reverse the tolerance to b-agonists in mast cells in vitro [45]. This suggests that regular treatment with inhaled corticosteroids should prevent the tolerance to the mast cell stabilising effects of b 2 -agonists and this may be an important mechanisms in reducing asthma exacerbations, as in the FACET study, and with combination inhalers.…”
Section: Mast Cell Stabilisationmentioning
confidence: 99%
“…Interestingly, glucocorticoids tend to reverse many of these effects, demonstrating the highly beneficial potential of combined b 2 -agonist/corticosteroid therapy [6]. Indeed, glucocorticoids enhance b 2 -adrenoceptor expression and function [178][179][180], resensitise b 2 -adrenoceptors [181], increase Gsa expression [182], enhance eosinophil apoptosis [173] and reverse the upregulation of NK-2 receptor expression [175].…”
Section: Promiscuous G-protein Couplingmentioning
confidence: 99%